Strategi Pemasaran Digital Menggunakan Sistem Internet Endorsement Sebagai Upaya Dalam Meningkatkan Penjualan - Hasanuddin, Ananda; Delia, Egi Astuti; Bahari, Rizal; Ruci, Dewa (AKTIVA: Journal of Accountancy and Management, 2024)
Purpose: This research aims to understand how e-endorsements, which involve popular individuals or entities in product promotions, can increase consumer purchasing interest, build positive perceptions of products, and encourage purchase intentions.Methodology: The research method used in this research is a qualitative approach that focuses on literature reviews. Researchers collect and analyze existing data from various sources to understand the effectiveness of e-endorsements as a digital marketing strategy. Research Findings: E-endorsement is an effective digital marketing strategy in digital business. This strategy involves using popular individuals or entities to promote a product, which can increase purchasing interest, build positive perceptions of the product, and encourage purchase intent. Contribution/Originality/Novelty: The contribution of this research lies in an in-depth analysis of the influence of e-endorsements in digital marketing, especially in the context of growing digital businesses. Its originality comes from the focus on discussing influencers with high popularity and trust as a promotional tool, which has not been researched much before. The novelty of this research lies in the latest observations of trends in e-commerce and social media, as well as an assessment of the potential of e-endorsements as a business opportunity for resellers and dropshippers. Tujuan Penelitian: Penelitian ini bertujuan untuk memahami bagaimana e-endorsement, yang melibatkan individu atau entitas populer dalam promosi produk, dapat meningkatkan minat beli konsumen, membangun persepsi positif terhadap produk, dan mendorong keinginan pembelian.Metodologi: Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif yang berfokus pada tinjauan literatur. Peneliti mengumpulkan dan menganalisis data yang ada dari berbagai sumber untuk memahami efektivitas e-endorsement sebagai strategi pemasaran digital.Temuan Penelitian: E-endorsement merupakan strategi pemasaran digital yang efektif dalam bisnis digital. Strategi ini melibatkan penggunaan individu atau entitas populer untuk mempromosikan produk, yang dapat meningkatkan minat beli, membangun persepsi positif produk, dan mendorong keinginan pembelian.Kontribusi/Orisinalitas/Kebaruan: Kontribusi penelitian ini terletak pada analisis mendalam tentang pengaruh e-endorsement dalam pemasaran digital, khususnya dalam konteks bisnis digital yang berkembang. Originalitasnya datang dari fokus pada pembahasan mengenai influencer dengan popularitas tinggi dan kepercayaan sebagai alat promosi, yang belum banyak diteliti sebelumnya. Kebaharuan penelitian ini terletak pada pengamatan terkini terhadap tren dalam e-commerce dan media sosial, serta penilaian terhadap potensi E-endorsement sebagai peluang bisnis bagi reseller dan dropshipper.